Tropem magii słowa w literaturze chorwackiej i serbskiej XX wieku - Czapik-Lityńska, Barbara (Wydawnictwo Naukowe UAM, 2013)
The essay titled „Pursuing the Magic of Words in the Twentieth-Century’s Croatian and Serbian Literature” discusses transformations of the awareness of the avant-garde and postmodernism from the perspective of its relation to magic thinking. The essay advances a vision of poetic language and the main figures of the avant-garde’s imagination, especially the aesthetic conceptualizations of the messianic archetype. The avant-garde thinking about the world of unity (of the world-man-language) is utopian and not infrequently magic-esoteric. Postmodernism deconstructs symbolic language; it does not share the avantgarde’s belief in the existential and creative power of imagination and the word. The virtual culture of postmodernism reduces the value of the language sign and the referential function of language; it disenchants the conceits of the magic word.
Pursuing the Magic of Words in the Twentieth-Century’s Croatian and Serbian Literature
Keywords: magic thinking; post-magic thinking; aesthetic experience; cultural experience; speech communication; extraverbal communication; imagination; word; symbol; sign; metamorphic identity